Microglial state changes in response to LM11A‐31 promote recovery in a tauopathy mouse model of Alzheimer's Disease. (20th December 2022) - Butler, Robert R.; Yang, Tao; Tran, Kevin C; Johnson, William A; Liu, Harry; Leng, Song Albert; Massa, Stephen M.; Longo, Frank M.
Abstract: Background: Tau pathologies in Alzheimer's Disease (AD) contribute to neurodegeneration and synaptic degeneration via a variety of mechanisms. Neurotrophic signaling pathways present an avenue to counteract degenerative mechanisms via receptor modulating compounds, such as the p75 NTR ‐targeted small molecule LM11A‐31 (C31). Treatment with C31 in tauopathy models causes reductions in tau aggregation and microglial activation, restoration of synaptic plasticity, and prevention of synaptic spine loss. Using tauopathy model tau P301S mice (PS19), we examined the impact of long‐term dosing with C31 at the single‐cell transcriptional level to better understand the cell types and cellular mechanisms affected by treatment. Methods: PS19 and age‐matched (Wt) mice were dosed with either C31 or vehicle for 3 months starting at 6 months of age, when tau pathology was well established. Whole cortex was isolated for nuclear extraction and single‐nucleus RNA‐sequencing. Analysis Results: Clustering microglia for cell type annotation revealed treatment group‐specific microglial subclusters (Figure 1). Further, microglial gene expression across experimental groups showed a strong inverse correlation (R = ‐0.647; p < 1.01e‐78) between C31 differential expression and PS19 differential expression in genes nominally significant (p < 0.05) for both (Figure 2). In particular, microglial genes that were downregulated in the PS19 tauopathy model and upregulated by C31 were enriched for those falling into GO categories including "synapse organization" and "cell junction organization" (p‐adj: 8.95e‐20, 2.66e‐17). Conversely, expression that was up in PS19 tauopathy and down in C31 showed enrichment for "small GTPase mediated signal transduction", and "cell junction disassembly" (p‐adj: 8.59e‐05, 0.0431). Conclusion: These findings demonstrate differences in microglial gene expression between Wt and PS19 mice some of which may be reversed by C31. Loss of homeostatic microglia has been previously associated with AD neurodegeneration, improper dendritic spine formation and inability to maintain synaptic structure. Our findings support the hypothesis that loss of homeostatic microglia exacerbates synaptic dysfunction, and their recovery may be one potential mechanism by which C31 can restore synaptic plasticity.